The answer would be 9 because
Answer:
Step-by-step explanation:
x+6/11=10/11
This is a linear equation, because x has no power, so it will be solved by making x the subject of the equation.
Make x the subject
x+6/11=10/11
x=-6/11+10/11
x=10/11-6/11
Since both fractions have the same denominator, the LCM remains 11
x=(10-6)/11
x=4/11
To check if the answer is correct, we substitute x for 4/11 in the equation. And both sides of the equation must be equal
x+6/11=10/11
4/11+6/11=10/11
(4+6)/11=10/11
10/11=10/11
Answer:
A) is correct
Step-by-step explanation:
Step-by-step explanation:
x/3-2/5=2x/15-3x
5x-6=2x-9
5x-2x=-9+6
3x=-3
3x/3=-3/3
x=-1